2016
DOI: 10.1302/0301-620x.98b5.36887
|View full text |Cite
|
Sign up to set email alerts
|

Total ankle arthroplasty versus ankle arthrodesis

Abstract: TAA preserves more anatomic sagittal plane motion and provides greater pain relief and better patient-perceived outcomes compared with ankle arthrodesis. Cite this article: Bone Joint J 2016;98-B:634-40.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(29 citation statements)
references
References 21 publications
2
26
0
1
Order By: Relevance
“…Although ankle arthrodesis has been used traditionally to treat end-stage ankle arthritis, the clinical outcomes comparing arthrodesis to TAA have been reported in multiple studies. 20212223 With regard to comparing quoted consumer prices for the two procedures, our results showed no notable difference between ankle arthrodesis and TAA. This conclusion differs from our hypothesis and other price comparisons found in the literature.…”
Section: Discussionmentioning
confidence: 57%
“…Although ankle arthrodesis has been used traditionally to treat end-stage ankle arthritis, the clinical outcomes comparing arthrodesis to TAA have been reported in multiple studies. 20212223 With regard to comparing quoted consumer prices for the two procedures, our results showed no notable difference between ankle arthrodesis and TAA. This conclusion differs from our hypothesis and other price comparisons found in the literature.…”
Section: Discussionmentioning
confidence: 57%
“…Bei aller Einschränkung ist die erreichte Beweglichkeit besser als nach einer Arthrodese des oberen Sprunggelenks [23]. Entsprechend ist nach Implantation einer OSG-Endoprothese eine bessere Funktion beim Steigen von Treppen und beim Gehen auf unebenem Untergrund als nach einer Arthrodese erreichbar [24].…”
Section: Merkeunclassified
“…Therefore, many authors promote total-ankle-arthroplasty (TAA) as an attractive alternative to increase function and mobility. While first and second-generation TAA showed poor survival rates and clinical outcomes measures due to a high number of complications [10,11], current generations of TAA show promising results: several authors reported a reduction in complication rates leading to increased survival as well as improved clinical outcome measures like the American Orthopaedic Foot and Ankle Society (AOFAS) score [12][13][14][15][16][17]. Hence, TAA gained popularity within the last few years [18][19][20].…”
Section: Introductionmentioning
confidence: 99%